Medical Ahadith in of Al-Raniri's Bustan Al-Salatin Chapter 7 Fasl 3 - Mohd Shafri, Mohd Affendi; Rosdin, Muhammad Amir Ashraf; Mohamad, Hasbullah; Muhammad Yahya, Hermansyah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
The incorporation of hadith in Islamic medical literature is a common phenomenon. In the Malay world, Bustan al-Salatin in its Chapter 7 Faṣl 3 (BSVII-III) contains the greatest number of these medical ahadith among Malay medical manuscripts. This paper presented a preliminary study on the ahadith typology and sources and their use pattern in BSVII-III. Ahadith in two extant manuscripts of BSVII-III from Aceh were extracted, listed and compared. Then, these medical ahadithwere checked using al-Maktabah al-Waqfiyyah online resource and al-Maktabah al-Shamilahhadithsearch software to find their sources. The methodology employed by al-Rānīrī in incorporating these medical ahadith were also analysed. It was found that there are 40 narrations referenced as ḥadīth in this faṣl, distributed on four topics on anatomy (n=3), the principles of medicine (n=14), materia medica (n=28) and medical hikayat (medical marvels) (n=2). 70% of them are confirmed as hadith, five are confirmed as the sayings of other figures, whereas seven narrations have unconfirmed origins. These ahadith were mostly narrated without providing the source or the full matn or sanad of narrators. Hence, it is a challenge in tracing the reliability and status of the unconfirmed ahadith. al-Rānīrī’s liberal use of ahadith in BSVII-III may be attributed to the fact that this text is not meant to be a ḥadīth text and the use of ahadith are primarily to provide support to the known medical management of health and disease. BSVII-III remains an exciting text to be explored, given its importance in integrating medical and religious sciences, Islamisation of knowledge and the study of hadithin the Malay Archipelago.